The Interiorization of COVID-19 in the cities of Pernambuco State, Northeast of Brazil - Rosalva Raimundo da Silva; Geyssyka Morganna Soares Guilhermino; Barnabé Lucas de Oliveira Neto; José Bonifácio de Lira Neto (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to analyze how the disseminationof COVID-19 occurred in the cities of Pernambuco State, Northeast in Brazil. Methods: descriptive, exploratory and quantitative study whose units of analysis were the 184 cities and Fernando de Noronha Archipelago which constitutes the state of Pernambuco. Geoprocessing techniques used QGis 3.14.16 and were presented in figures. Results: the first city to register a case of COVID-19 was Recife, in 129 days there were already confirmed cases of the disease in all the cities in the state and including Fernando de Noronha Archipelago. Only 117 cities informed the patients' sexin public reports since the first case and only 88 cities mentioned the patients ' age. Conclusion: there was a fast spread of COVID-19 in the state of Pernambuco, showing the inability of the Health Surveillance services to control the transmission, especially in smalltowns.